Pollution control mechanism of national water network with water quality differences based on differential game and case study - Yang, Yaohong; Yang, Yang; Yang, Shuwen; Zhang, Junhua (Scientific reports, 2025)
The construction of the national water network optimizes water resource allocation but also causes a redistribution of pollutants due to water quality differences, posing urgent challenges for water pollution management. Taking the South-to-North Water Diversion Project and Yangtze-to-Hanjiang River Water Diversion Project (YHRWDP) as an example and considering the pressure brought by the redistribution of pollutants to the polluting enterprises (PE) and water diversion enterprises (WDE) situated in areas where pollution is aggravated, a differential game model of pollution control among the central government, water-supply area (WSA), PE and WDE is constructed based on the cost-sharing mechanism. The results show that: (1) The pressure coefficient has an apparent negative correlation with the effort level of the affected subject. (2) An increase in the amount of pollution elimination per unit of pollution control effort of WSA and PE will lead to their own investment in more efforts to improve the ecology of the basin, thus benefiting all participants in the system. (3) The cost-sharing rate of the central government on the WSA of the YHRWDP, the PE, and the WDE is influenced by several factors, which shows a stable monotonically increasing or decreasing relation. The results are an useful supplement to the research on natural river pollution control, and can also provide a reference for designing pollution control mechanisms of national water network.